Tissue sodium accumulation and peripheral insulin sensitivity in maintenance hemodialysis patients. Issue 3 (1st February 2017) - Deger, Serpil Muge; Wang, Ping; Fissell, Rachel; Ellis, Charles D.; Booker, Cindy; Sha, Feng; Morse, Jennifer L.; Stewart, Thomas G.; Gore, John C.; Siew, Edward D.; Titze, Jens; Ikizler, Talat Alp
Abstract: Background: Recent data suggest that sodium (Na + ) is stored in the muscle and skin without commensurate water retention in maintenance hemodialysis (MHD) patients. In this study, we hypothesized that excessive Na + accumulation would be associated with abnormalities in peripheral insulin action. Methods: Eleven MHD patients and eight controls underwent hyperinsulinemic–euglycemic–euaminoacidemic clamp studies to measure glucose (GDR) and leucine disposal rates (LDR), as well as lower left leg 23 Na magnetic resonance imaging to measure Na + concentration in the muscle and skin tissue. Results: The median GDR and LDR levels were lower, and the median muscle Na + concentration was higher in MHD patients compared with controls. No significant difference was found regarding skin Na + concentration between group comparisons. Linear regression revealed inverse relationships between muscle Na + concentration and GDR and LDR in MHD patients, whereas no relationship was observed in controls. There was no association between skin Na + content and GDR or LDR in either MHD patients or controls. Conclusions: These data suggest that excessive muscle Na + content might be a determinant of IR in MHD patients, although the causality and mechanisms remain to be proven.